Choice of Empirical Antibiotic Therapy and Adverse Outcomes in Older Adults With Suspected Urinary Tract Infection: Cohort Study. (18th January 2019) - Ahmed, Haroon; Farewell, Daniel; Francis, Nick A; Paranjothy, Shantini; Butler, Christopher C
Abstract: Background: Nitrofurantoin is widely recommended for empirical treatment of urinary tract infection (UTI), but primary care clinicians may prescribe alternative antibiotics to improve prognosis in older, sicker patients. We assessed whether prescribing alternative antibiotics was associated with reduced risk of adverse outcomes in older patients. Methods: This retrospective cohort study included patients aged ≥65 years empirically treated for a UTI with nitrofurantoin, cefalexin, ciprofloxacin, or co-amoxiclav. We matched patients on their propensity to receive a nitrofurantoin prescription and used mixed-effects logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for reconsultation and represcription (proxy for treatment failure), hospitalization for UTI, sepsis, or acute kidney injury, and death. Results: We identified 42 298 patients aged ≥65 years prescribed empirical nitrofurantoin, cefalexin, ciprofloxacin, or co-amoxiclav for a UTI. Compared with nitrofurantoin, patients prescribed cefalexin, ciprofloxacin, or co-amoxiclav had lower odds of reconsultation and represcription (OR for cefalexin = 0.85, 95% CI = 0.75–0.98; OR for ciprofloxacin = 0.48, 95% CI = 0.38–0.61, OR for co-amoxiclav = 0.77, 95% CI = 0.64–0.93). Patients prescribed cefalexin or ciprofloxacin had greater odds of hospitalization for sepsis (OR for cefalexin = 1.89, 95% CI = 1.03–3.47; OR for ciprofloxacin = 3.21, 95% CI = 1.59–6.50), and patients prescribed cefalexin had greater odds of death (OR = 1.44, 95% CI = 1.12–1.85). Conclusions: Compared with nitrofurantoin, prescribing of alternative antibiotics for UTI in older people may be associated with lower rates of treatment failure but was not associated with reduced risk of UTI-related hospitalization or death.